Gender Politics of “Illiberal Pragmatics” in the Polish Defense Sector - Grzebalska, Weronika (2022)
Since 2015, the illiberal Law and Justice (Prawo i Sprawiedliwość [PiS]) government in Poland has engaged in campaigns against “gender ideology,” rolling back several equality mechanisms and provisions, and mainstreaming traditionalist values into state policy. Following from this, scholarship has predominantly addressed PiS gender politics through the concepts of anti-gender backlash and gender backsliding. Against this background, Polish defense policy constitutes a puzzling realm that significantly escapes these frameworks, revealing instead a mix of backsliding, institutional and discursive continuity, and positive gender change. While the displacement of the Plenipotentiary for Equal Treatment office has erased similar bodies in the defense sector, the government has swiftly created a National Action Plan on Women, Peace and Security, strengthened the Armed Forces Women’s Council, and continued prior policy and discourse on women’s service. Meanwhile, the increased defense preparations following the war in eastern Ukraine have doubled women’s percentage in the armed forces, partially regendering the very idea and practice of defense. To explore this ambiguity, the article draws from feminist institutionalism and multi-sited sociological methods. It proposes to move beyond backlash towards the analytical concept of illiberal pragmatics—a complex, gendered logic of governance which seeks to balance illiberals’ dedication to national sovereignty with pragmatic political, security, demographic, and economic considerations. Under illiberal pragmatics, women’s interests are pursued within a more conservative framework, with gender norms simultaneously upheld and destabilized across different realms. Nevertheless, the key feature of illiberal gender politics lies not in backsliding, but in a pragmatic balancing act between national integrity and structural pressures for change.